Hubungan Kualitas Tidur Terhadap Konsentrasi Belajar Mahasiswa Fakultas Kedokteran Universitas Baiturahmah Padang Angkatan 2018 - Syarifah Fazhilah Djamalilleil; Rosmaini Rosmaini; Nadia Purnama Dewi (Health and Medical Journal, 2021)
Introduction: The lack of concern toward sleep quality is frequently found on students of high schoold, hectic workers and college students, the impacts of sleep lack could affect to learning concentration. Aims: To find out the correlation between sleep quality and learning concentration ,students of medical faculty, University of Baiturrahmah Padang in Second Year.Method: The scope of this study covers the field of general medical science, this study was conducted at the Faculty of Medical, University of Baiturahmah Padang on April 2019 to January 2020. The type of this study was descriptive analytic study with cross sectional study design. Affordable population in the study were students of the Faculty of Medical, University of Baiturahmah in second year, the amount was 150 people with 76 samples by using random sampling technique. Univariate data analysis was presented in the form of frequency and percentage distributions as well as bivariate analysis using chi-square test and data processing using computerized SPSS program version 24.0. Result: Based on the results of the study, People who had the poor sleep quality are 53 people (69.7%), had a poor learning concentration are 42 people (55.3%) and there was a correlation between sleep quality and learning concentration of students at the Faculty of Medical, University of Baiturrahmah, Padang in second year P = 0.034 <0.05.Conclusion: It is proven that there was a correlation between sleep quality and the learning concentration of students at the Faculty of Medical, University of Baiturrahmah Padang, Second year.